MiR‐802 causes nephropathy by suppressing NF‐κB‐repressing factor in obese mice and human. Issue 4 (7th February 2019) - Sun, Da; Chen, Jia; Wu, Wei; Tang, Ju; Luo, Li; Zhang, Kun; Jin, Libo; Lin, Sue; Gao, Yitian; Yan, Xiaoqing; Zhang, Chi
Abstract: Obesity is associated with significant microvascular complications including renal injuries and may induce end‐stage renal disease. Emerging studies have demonstrated microRNAs (miRNAs) are potential mediators in the pathophysiological process of nephropathy. The present study aimed to investigate the role of miR‐802 in obesity‐related nephropathy and potential molecular mechanisms. Through utilizing obese mouse model and human subjects, we explored the therapeutic benefits and clinical application of miR‐802 in protecting against nephropathy. Renal miR‐802 level was positively correlated with functional parameters, including blood urea nitrogen and creatinine in obese mice. Specific silencing of renal miR‐802 improved high fat diet (HFD)‐induced renal dysfunction, structural disorders and fibrosis. The up‐regulated inflammatory response and infiltrated macrophages were also significantly decreased in miR‐802 inhibitor‐treated obese mice. Mechanistically, miR‐802 directly bond to 3ʹ‐UTR of NF‐κB‐repressing factor (NRF) and suppressed its expression. In clinical study, the circulating miR‐802 level was significantly increased in obese subjects, and positively correlated with plasma creatinine level but negatively correlated with creatinine clearance. Taken together, our findings provided evidence that miR‐802/NRF signalling was an important pathway in mediating obesity‐related nephropathy. It is a possible useful clinical approach of treating miR‐802 inhibitor to combat nephropathy.